Falando fora dos autos: a comunicação pública e o protagonismo do judiciário - Silva Junior, Nivaldo da (Universidade Federal de São Carlos, 2025)
This work focuses on analyzing how public communication occurred among the actors of the judiciary, particularly the STF and the TSE, during the electoral period from 2022 to January 2023, investigating how this communication contributed to judicial protagonism. The context unfolds in a setting of general elections, marked by a high degree of polarization and the use of strategies to cast doubt on the integrity of the electronic voting process. Thus, how did the STF, the TSE, and their justices communicate during the 2022 elections, especially regarding the issue of fraud in electronic voting machines? We argue that judicial protagonism is a concept encompassing phenomena such as the politicization of the judiciary, the judicialization of politics, and judicial activism. Protagonism may manifest itself in communication as one of its facets. Judicial protagonism is treated as a process that begins with the 1988 Constitution, includes the defense of citizenship rights, and reaches its peak in the punitive dimension of accountability, exemplified by Operation Car Wash. We argue that the mediatization of the judiciary leads to the celebritization of its actors. The research employed mixed methods, including content and textual analysis, focusing on publications from the G1 and R7 news portals, as well as posts by justices on social network X. The results indicate that communication during the analyzed period was personalistic, with Alexandre de Moraes emerging as a central figure representing the defense of the electronic voting process. While the STF consolidated itself as a unified court in response to authoritarian threats, the electoral courts coalesced around Moraes in electoral matters. It is concluded that communication, whether personalistic or institutional, reflects and amplifies judicial protagonism, underscoring the importance of examining the media role of judicial institutions in contexts of political polarization.
Speaking beyond the case files: public communication and the judiciary's protagonism
Keywords: Comunicação pública; Protagonismo do judiciário; Processo eleitoral; STF; TSE; Eleições 2022; Public communication; Judicial protagonism; Electoral process; 2022 elections; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO